PENGARUH REFERENDUM BREXIT TERHADAP TINDAKAN RASIAL PEREMPUAN BAME KULIT HITAM DI INGGRIS TAHUN 2016-2020 - putri, roviela agus kurnia; Resen, Putu Titah Kawitri; Prameswari, Anak Agung Ayu Intan (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2022)
The Brexit Referendum is interpreted as an increase in racism and indicated the success of Euroscepticism and xenophobia in the UK.  The UK’s exit from the European Union (EU), has the potential to abolish EU-derived policies as a legal buffer for Britain’s equality and anti-discrimination rights. Therefore, black BAME women in the UK are the most disadvantaged subjects from the outcome of the Brexit Referendum. The data collected in this study were obtained from the results of the literature study, with the theoretical framework of New Racism and Black Feminism on the Brexit Referendum issue. This research ultimately provides an answer that the Brexit Referendum increases the racism experienced by the black BAME women in the UK through various kinds of abolition of policies that protect BAME women in the UK, such as the EU Charter of Fundamental Rights and the Anti-Discrimination Act, passed down by the EU.